Aplikasi Pencari Tempat Magang Berbasis Android Menggunakan Metode Agile Scrum - Firdaus, Ammar Musthofa; Prabowo, Dedy Agung (Jurnal Informatika UPGRIS, 2022)
Internship is a process that is an obligation to be carried out in the academic process at the Telkom Institute of Technology Purwokerto, however with various media sources used in finding internships, students have problems in finding suitable internships. This study aims to apply Agile Scrum and Simple Additive Weighting in making applications to find a suitable internship place. Agile Scrum is used as a method of continuous application development, Simple Additive Weighting is used as a method in determining recommendations based on existing input. Application testing is carried out using Black Box Testing which tests the success of the function in carrying out its scenario and User Acceptance Test which is used as a benchmark in the suitability of the application with user needs. The results of this study are an android application in the form of an apk that was tested using Black Box Testing and got valid results in all scenarios and had a score of 87% on the User Acceptance Test